Ni-W / LDH-PMCA composite coating, plating solution and preparation method of Ni-W / LDH-PMCA composite coating
By introducing LDH-PMCA nanosheets into the Ni-W plating layer, Ni-W/LDH-PMCA composite plating layer is formed, the problem of insufficient protection effect of Ni-W plating in harsh environments is solved, and the corrosion resistance and resistance of the plating layer are achieved Improved abrasiveness and density.
Patent Information
- Application Number
- CN202411449368.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-07
AI Technical Summary
The existing Ni-W plating is insufficient in corrosion media or high-strength mechanical wear environments, and it is difficult to effectively integrate nanomaterials to improve performance.
Using Ni-W/LDH-PMCA composite plating, LDH-PMCA nanosheets with high lubrication and ion exchange capability are introduced into the Ni-W plating layer, and LDH-PMCA nanosheets are prepared by calcining, stirring, centrifugation and drying. , and combine it with Ni-W plating solution to form a composite plating layer through electroplating technology.
It significantly improves the corrosion resistance, wear resistance and density of the coating, enhances the protection ability of the metal substrate, and improves the hardness and protection performance of the coating.
Smart Images

Figure CN119265674A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, and in particular to a Ni-W / LDH-PMCA composite coating, a plating solution and a preparation method thereof. Background Art
[0002] As an effective surface treatment method, coating technology is widely used to improve the protective performance of substrates. Among them, Ni-W coating has attracted much attention due to its good corrosion resistance and certain wear resistance. However, under certain harsh conditions, the performance of pure Ni-W coating still faces challenges, especially long-term exposure to corrosive media or high-intensity mechanical wear environment, and its protective effect needs to be further improved.
[0003] Layered double hydroxide (LDH), as a new type of nanomaterial, has become a research hotspot in the field of materials science due to its unique layered structure, high specific surface area, excellent chemical stability and controllable ion exchange properties. In particular, by introducing organic or inorganic functional molecules for modification, not only can the basic properties of LDH be retained, but also new functions can be given to the material, such as improving interface bonding and adjusting pore structure, thus showing great application potential in the field of coating.
[0004] Although existing studies have shown that incorporating nanoparticles into metal coatings can significantly enhance the physical and chemical properties of the coatings, how to efficiently integrate LDH nanomaterials into Ni-W coating systems remains a technical challenge that needs to be solved. In existing technologies, there are often problems such as uneven dispersion of nanoparticles, weak interface bonding, and difficulty in controlling the coating structure, which limit the optimization of the overall performance of the coating. Summary of the invention
[0005] In view of the above problems, the present invention aims to provide a Ni-W / LDH-PMCA composite coating, a plating solution and a preparation method thereof.
[0006] The technical solution of the present invention is as follows:
[0007] On the one hand, a Ni-W / LDH-PMCA composite coating is provided, comprising a base coating and a reinforcement phase, wherein the base coating is a Ni-W coating, and the reinforcement phase is an LDH-PMCA nanosheet.
[0008] Preferably, in terms of weight percentage, the content of Ni is 67-72%, the content of W is 27.83-32.67%, and the content of LDH-PMCA nanosheets is 0.17-0.33%.
[0009] Preferably, the LDH-PMCA nanosheets are obtained by the following steps: obtaining LDH nanosheets and calcining the LDH nanosheets; placing the calcined LDH nanosheets and p-methylcinnamic acid in a mixed solution of deionized water and ethanol for stirring, centrifugation and drying to obtain the LDH-PMCA nanosheets.
[0010] Preferably, during calcination, the temperature is 450-530°C and the time is 1-3h; during stirring, the stirring is performed at a rotation speed of 300-500rpm for 25-40min; during centrifugation, the centrifugal speed is 7000-9000rpm; during drying, the drying temperature is 50-70°C.
[0011] Preferably, the mass ratio of the calcined LDH nanosheets to the p-methylcinnamic acid is 100:1.5-6; the volume ratio of the deionized water to ethanol is 1:1; and the particle size of the LDH-PMCA nanosheets is 100-200 nm.
[0012] On the other hand, a Ni-W / LDH-PMCA composite plating solution is also provided, comprising a Ni-W plating solution and LDH-PMCA nanosheets in a mass ratio of 100:0.02-0.3.
[0013] Preferably, the Ni-W plating solution is a sulfate-type Ni-W plating solution or an aminosulfonate-type Ni-W plating solution.
[0014] Preferably, it includes 10-20 g / L nickel sulfate hexahydrate, 40-55 g / L sodium tungstate dihydrate, 10-20 g / L sodium bromide or sodium fluoride, 130-160 g / L trisodium citrate dihydrate, 20-35 g / L ammonium chloride, 1-2 g / L saccharin, 0.1-0.2 g / L surfactant, and 0.2-3 g / L LDH-PMCA nanosheets;
[0015] The Ni-W / LDH-PMCA composite plating solution is prepared by the following steps:
[0016] Prepare a Ni-W plating solution, wherein the Ni-W plating solution includes 10-20 g / L of nickel sulfate hexahydrate, 40-55 g / L of sodium tungstate dihydrate, 10-20 g / L of sodium bromide or sodium fluoride, 130-160 g / L of trisodium citrate dihydrate, and 20-35 g / L of ammonium chloride;
[0017] Weighing LDH-PMCA nanosheets at a concentration of 0.2-3 g / L, and placing them in the Ni-W plating solution, and then adding 1-2 g / L saccharin and 0.1-0.2 g / L surfactant;
[0018] The Ni-W / LDH-PMCA composite plating solution was obtained by water bath ultrasonication for 15 to 20 minutes and then probe ultrasonication for 15 to 30 minutes.
[0019] On the other hand, a method for preparing a Ni-W / LDH-PMCA composite coating is also provided, comprising the following steps:
[0020] S1: obtaining a metal substrate and pre-treating the metal substrate;
[0021] S2: preparing a Ni-W / LDH-PMCA composite plating solution, and heating the Ni-W / LDH-PMCA composite plating solution to 60-80° C.;
[0022] S3: placing the pretreated metal substrate into the Ni-W / LDH-PMCA composite plating solution at a temperature of 60-80° C. for electroplating to obtain the Ni-W / LDH-PMCA composite coating.
[0023] Preferably, in step S3, when electroplating is performed, the pH of the Ni-W / LDH-PMCA composite plating solution is 7-8, the stirring speed is 300-400 rpm, the temperature is 60-80°C, and the current density is 5A / dm 2 .
[0024] The beneficial effects of the present invention are:
[0025] The present invention uses LDH-PMCA nanosheets with high lubricity and ion exchange capacity as a reinforcing agent to enhance the Ni-W coating, which can greatly improve the coating's ability to protect the metal substrate. Specifically, after the PMCA material modifies LDH, the ion exchange capacity of the LDH material will be enhanced, and the exchange capacity between the LDH interlayer anions and the corrosive anions in the outside world will be improved, which will enhance the corrosion resistance of the Ni-W / LDH-PMCA composite coating; the self-lubricating effect of the layered material will enhance the wear resistance of the Ni-W / LDH-PMCA composite coating; in addition, the introduction of the LDH-PMCA material into the coating will have the effects of dispersion strengthening and fine grain strengthening, thereby improving the hardness and density of the coating. In summary, the Ni-W / LDH-PMCA composite coating has the advantages of high hardness, corrosion resistance, wear resistance, and good density. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0027] Figure 1 Schematic diagram of the preparation process of the Ni-W / LDH-PMCA composite coating in Example 1;
[0028] Figure 2 Schematic diagram of X-ray diffraction and Fourier infrared of LDH nanosheets and LDH-PMCA nanosheets in Example 1; wherein, Figure 2 (a) is a schematic diagram of X-ray diffraction; Figure 2 (b) is a schematic diagram of Fourier infrared;
[0029] Figure 3 It is a high-resolution transmission electron microscope image of LDH nanosheets and LDH-PMCA nanosheets in Example 1 and the corresponding mapping diagram; wherein, Figure 3 (a) is a transmission electron microscopy diagram of LDH nanosheets; Figure 3 (b) is a schematic diagram of a high-resolution transmission electron microscope image of LDH nanosheets; Figure 3 (c) is a schematic diagram of a high-resolution transmission electron microscope image of LDH nanosheets; Figure 3 (d) is a transmission electron microscopy diagram of LDH-PMCA nanosheets; Figure 3 (e) is a schematic diagram of high-resolution transmission electron microscopy of LDH-PMCA nanosheets; Figure 3 (f) is a schematic diagram of high-resolution transmission electron microscopy of LDH-PMCA nanosheets;
[0030] Figure 4 It is a schematic diagram of the SEM scanning results of the coatings of Example 1, Comparative Example 1 and Comparative Example 2; wherein, Figure 4 (a) is a SEM schematic diagram of pure Ni-W coating; Figure 4 (b) is a SEM schematic diagram of pure Ni-W coating; Figure 4 (c) is a SEM schematic diagram of the Ni-W / LDH coating; Figure 4 (d) is the SEM schematic diagram of Ni-W / LDH coating; Figure 4 (e) is a SEM schematic diagram of the Ni-W / LDH-PMCA coating; Figure 4 (f) is the SEM schematic diagram of Ni-W / LDH-PMCA coating;
[0031] Figure 5 This is a schematic diagram of the mapping results of the coating in Example 1; wherein, Figure 5 (a) is a SEM schematic diagram of Ni-W / LDH-PMCA coating; Figure 5 (b) is the SEM schematic diagram of Ni-W / LDH-PMCA coating; Figure 5 (c) is the SEM schematic diagram of Ni-W / LDH-PMCA coating;
[0032] Figure 6 This is a schematic diagram of the X-ray photoelectron spectroscopy results of the coating in Example 1; wherein, Figure 6 (a) is a schematic diagram of the full XPS spectrum of Ni-W / LDH-PMCA coating; Figure 6 (b) is a schematic diagram of the C1s fine spectrum of the Ni-W / LDH-PMCA coating XPS;
[0033] Figure 6 (c) Schematic diagram of Ni 2p fine spectrum of XPS of Ni-W / LDH-PMCA coating; Figure 6 (d) Schematic diagram of the W 4f fine spectrum of the XPS of Ni-W / LDH-PMCA coating; Figure 6 (e) Schematic diagram of the XPS Mg 1s fine spectrum of Ni-W / LDH-PMCA coating; Figure 6 (f) is a schematic diagram of the Al 2p fine spectrum of the Ni-W / LDH-PMCA coating XPS;
[0034] Figure 7 Schematic diagram of X-ray diffraction results of the coatings of Example 1, Comparative Example 1 and Comparative Example 2; wherein, Figure 7 (a) is the XRD schematic diagram; Figure 7 (b) is a schematic diagram of grain size;
[0035] Figure 8 It is a schematic diagram of the electrochemical impedance and polarization results of the coatings of Example 1, Comparative Example 1 and Comparative Example 2; wherein, Figure 8 (a) is a schematic diagram of electrochemical impedance spectroscopy; Figure 8 (b) is a schematic diagram of the Bode curve; Figure 8 (c) is a schematic diagram of the electrochemical polarization curve; Figure 8 (d) is the schematic diagram of the equivalent circuit;
[0036] Fig. 9 It is a schematic diagram of the average friction coefficient and hardness results of the coatings of Example 1, Comparative Example 1 and Comparative Example 2; wherein, Fig. 9 (a) is a schematic diagram of the friction curve; Fig. 9 (b) is a schematic diagram of the average friction coefficient; Fig. 9 (c) is a schematic diagram of microhardness;
[0037] Fig.10 The SEM results of the coatings of Example 1, Comparative Example 1 and Comparative Example 2 after friction are shown in FIG. Fig.10 (a) is the SEM diagram of the wear scar of pure Ni-W coating after friction; Fig.10 (b) is the SEM diagram of the wear scar of Ni-W / LDH coating after friction; Fig.10(c) is the SEM diagram of the wear scar of Ni-W / LDH-PMCA coating after friction;
[0038] Fig.11 It is a schematic diagram of the three-dimensional profile results after friction of the coatings of Example 1, Comparative Example 1 and Comparative Example 2; wherein, Fig.11 (a) Schematic diagram of the three-dimensional profile of the wear scar after friction of pure Ni-W coating; Fig.11 (b) Schematic diagram of the three-dimensional contour of the wear scar after friction of Ni-W / LDH coating; Fig.11 (c) Schematic diagram of the three-dimensional contour of the wear scar of Ni-W / LDH-PMCA coating after friction; Fig.11 (d) Schematic diagram of wear scar depth after friction of pure Ni-W coating; Fig.11 (e) Schematic diagram of the wear scar depth of Ni-W / LDH coating after friction; Fig.11 (f) Schematic diagram of the wear scar depth of Ni-W / LDH-PMCA coating after friction. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0040] On the one hand, the present invention provides a Ni-W / LDH-PMCA composite coating, comprising a base coating and a reinforcement phase, wherein the base coating is a Ni-W coating, and the reinforcement phase is an LDH-PMCA nanosheet.
[0041] In a specific embodiment, in terms of weight percentage, the content of Ni is 67-72%, the content of W is 27.83-32.67%, and the content of LDH-PMCA nanosheets is 0.17-0.33%.
[0042] In a specific embodiment, the LDH-PMCA nanosheets are obtained by the following steps: obtaining LDH nanosheets and calcining the LDH nanosheets; placing the calcined LDH nanosheets and p-methylcinnamic acid in a mixed solution of deionized water and ethanol for stirring, centrifugation, and drying to obtain the LDH-PMCA nanosheets.
[0043] In the above embodiment, the LDH-PMCA material with PMCA intercalation can be synthesized by utilizing the memory effect of the LDH nanosheet material itself through calcination. 2- The LDH nanosheets were added to the medium containing PMCA solution, so that the structure of the LDH nanosheets could be partially restored to an ordered layered structure, and part of the CO3 was replaced by PMCA. 2- Interlayer ions.
[0044] In addition, in the above embodiments, the solvent used is a mixed solution of deionized water and ethanol. This is mainly because PMCA has poor solubility in water but good solubility in ethanol. Ethanol is used to improve the solubility of PMCA in the solution.
[0045] In a specific embodiment, when calcining, the temperature is 450-530°C and the time is 1-3 hours; when stirring, stirring is performed at a speed of 300-500rpm for 25-40min; when centrifuging, the centrifugal speed is 7000-9000rpm; when drying, the drying temperature is 50-70°C.
[0046] In a specific embodiment, the mass ratio of the calcined LDH nanosheets to the p-methylcinnamic acid is 100:1.5-6; the volume ratio of the deionized water to ethanol is 1:1; and the particle size of the LDH-PMCA nanosheets is 100-200 nm.
[0047] On the other hand, the present invention also provides a Ni-W / LDH-PMCA composite plating solution, comprising a Ni-W plating solution and LDH-PMCA nanosheets in a mass ratio of 100:0.02-0.3.
[0048] In a specific embodiment, the Ni—W plating solution is a sulfate-type Ni—W plating solution or an aminosulfonate-type Ni—W plating solution.
[0049] In a specific embodiment, the Ni-W / LDH-PMCA composite plating solution includes 10-20 g / L nickel sulfate hexahydrate, 40-55 g / L sodium tungstate dihydrate, 10-20 g / L sodium bromide or sodium fluoride, 130-160 g / L trisodium citrate dihydrate, 20-35 g / L ammonium chloride, 1-2 g / L saccharin, 0.1-0.2 g / L surfactant, and 0.2-3 g / L LDH-PMCA nanosheets;
[0050] The Ni-W / LDH-PMCA composite plating solution is prepared by the following steps:
[0051] Prepare a Ni-W plating solution, wherein the Ni-W plating solution includes 10-20 g / L of nickel sulfate hexahydrate, 40-55 g / L of sodium tungstate dihydrate, 10-20 g / L of sodium bromide or sodium fluoride, 130-160 g / L of trisodium citrate dihydrate, and 20-35 g / L of ammonium chloride;
[0052] Weighing LDH-PMCA nanosheets at a concentration of 0.2-3 g / L, and placing them in the Ni-W plating solution, and then adding 1-2 g / L saccharin and 0.1-0.2 g / L surfactant;
[0053] The Ni-W / LDH-PMCA composite plating solution was obtained by water bath ultrasonication for 15 to 20 minutes and then probe ultrasonication for 15 to 30 minutes.
[0054] On the other hand, the present invention also provides a method for preparing a Ni-W / LDH-PMCA composite coating, comprising the following steps:
[0055] S1: obtaining a metal substrate and pre-treating the metal substrate;
[0056] S2: preparing a Ni-W / LDH-PMCA composite plating solution, and heating the Ni-W / LDH-PMCA composite plating solution to 60-80° C.;
[0057] S3: placing the pretreated metal substrate into the Ni-W / LDH-PMCA composite plating solution at a temperature of 60-80° C. for electroplating to obtain the Ni-W / LDH-PMCA composite coating.
[0058] In a specific embodiment, during electroplating, the pH of the Ni-W / LDH-PMCA composite plating solution is 7-8, the stirring speed is 300-400 rpm, the temperature is 60-80°C, and the current density is 5A / dm 2 .
[0059] Example 1
[0060] like Figure 1 As shown, a Ni-W / LDH-PMCA composite coating is prepared by the following steps:
[0061] (1) Preparation of LDH-PMCA nanosheets
[0062] LDH nanosheets were obtained and calcined at 500°C for 2h. 1g of the calcined LDH nanosheets and 4g of p-methylcinnamic acid were placed in a mixed solution of 50mL of deionized water and 50mL of ethanol, stirred at 400rpm, centrifuged at 8000rpm, and dried at 60°C to obtain LDH-PMCA nanosheets with a particle size of about 150nm.
[0063] (2) Obtaining a metal substrate and pre-treating the metal substrate
[0064] In this embodiment, when the metal substrate is pretreated, first, the metal substrate is polished using sandpaper of different mesh sizes, then ultrasonicated using deionized water and ethanol for 3 minutes respectively, and finally activated using glacial acetic acid for 30 seconds.
[0065] (3) Preparing a Ni-W / LDH-PMCA composite plating solution and heating the Ni-W / LDH-PMCA composite plating solution to 70° C.
[0066] In this embodiment, the Ni-W / LDH-PMCA composite plating solution includes 15.8 g / L nickel sulfate hexahydrate, 46.2 g / L sodium tungstate dihydrate, 15.5 g / L sodium bromide, 147 g / L trisodium citrate dihydrate, 26.7 g / L ammonium chloride, 1 g / L saccharin, 0.1 g / L surfactant, and 0.6 g / L LDH-PMCA nanosheets.
[0067] The Ni-W / LDH-PMCA composite plating solution is prepared by the following steps:
[0068] First, a Ni-W plating solution is prepared, wherein the Ni-W plating solution includes 15.8 g / L nickel sulfate hexahydrate, 46.2 g / L sodium tungstate dihydrate, 15.5 g / L sodium bromide, 147 g / L trisodium citrate dihydrate, and 26.7 g / L ammonium chloride;
[0069] Then, LDH-PMCA nanosheets were weighed at a concentration of 0.6 g / L and placed in the Ni-W plating solution, followed by 1 g / L saccharin and 0.1 g / L surfactant;
[0070] Finally, water bath ultrasound was performed for 15 minutes, and then probe ultrasound was used for 15 minutes to obtain the Ni-W / LDH-PMCA composite plating solution.
[0071] (4) Electroplating to obtain the Ni-W / LDH-PMCA composite coating
[0072] The pretreated metal substrate is placed in the Ni-W / LDH-PMCA composite plating solution at a temperature of 70°C for electroplating. In this embodiment, during electroplating, the pH of the Ni-W / LDH-PMCA composite plating solution is 7, the stirring speed is 350 rpm, the temperature is maintained at 70°C, the electroplating time is 45 min, and the current density is 5 A / dm 2 .
[0073] Example 2
[0074] Different from Example 1, the amount of LDH-PMCA nanosheets added in step (3) of this example is 0.2 g / L.
[0075] Example 3
[0076] Different from Example 1, the amount of LDH-PMCA nanosheets added in step (3) of this example is 1 g / L.
[0077] Example 4
[0078] Different from Example 1, the amount of LDH-PMCA nanosheets added in step (3) of this example is 2 g / L.
[0079] Example 5
[0080] Different from Example 1, the amount of LDH-PMCA nanosheets added in step (3) of this example is 3 g / L.
[0081] Comparative Example 1
[0082] Different from Example 1, step (1) is not performed in this comparative example, and the plating solution prepared in step (3) is a Ni-W plating solution. The Ni-W plating solution is different from the Ni-W / LDH-PMCA composite plating solution in that the LDH-PMCA nanosheets are not included therein. The coating obtained in this comparative example is a Ni-W coating.
[0083] In this comparative example, the Ni-W coating has a Ni content of 69.7% and a W content of 30.3% by weight.
[0084] Comparative Example 2
[0085] Different from Example 1, in this comparative example, LDH nanosheets only need to be obtained in step (1) without performing other operations in step (1); and the plating solution prepared in step (3) is a Ni-W / LDH composite plating solution. The Ni-W / LDH composite plating solution is different from the Ni-W / LDH-PMCA composite plating solution in that it includes LDH nanosheets instead of LDH-PMCA nanosheets. The coating obtained in this comparative example is a Ni-W / LDH composite coating.
[0086] In this comparative example, the Ni-W / LDH composite coating has, by weight percentage, 68.8% Ni, 30.99% W and 0.21% LDH nanosheets.
[0087] Comparative Example 3
[0088] Different from Example 1, in this comparative example, no calcination treatment is performed in step (1), and the synthesized material is not LDH-PMCA nanosheets, but LDH-SLS nanosheets directly synthesized by a hydrothermal method; and the plating solution in step (3) is Ni-W / LDH-SLS plating solution, not Ni-W / LDH-PMCA plating solution; the coating obtained in this comparative example is an LDH / SLS coating.
[0089] Test Case
[0090] The crystal structure of the LDH nanosheets obtained in Example 1 and the prepared LDH-PMCA nanosheets were observed by X-ray diffractometer and the molecular structure was observed by Fourier transform infrared spectrometer. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that by comparing the X-ray diffraction patterns of LDH and LDH-PMCA nanosheets, there is no obvious change in the peak positions of the two, indicating that the PMCA modification does not affect the crystal structure of LDH. By comparing the infrared spectra of the three, it can be seen that the PMCA material has been successfully introduced into the LDH material.
[0091] The LDH nanosheets obtained in Example 1 and the prepared LDH-PMCA nanosheets were observed using a high-resolution transmission electron microscope. The graphs and corresponding mappings were used to observe the microscopic morphology and element distribution. Figure 3 As shown. Figure 3 It can be seen that through the inverse Fourier transform, the lattice spacing of sample 3 has increased compared with sample 2, and the various elements are evenly distributed. The surface PMCA has been successfully inserted into the interlayer of the LDH material.
[0092] The microscopic morphology of the coatings of Example 1 and Comparative Examples 1-2 was observed by SEM, and the results were as follows: Figure 4 As shown. Figure 4 It can be seen that the coating of Example 1 has a significant grain refinement effect and a smaller size compared to the coatings of Comparative Examples 1 and 2, and there are no obvious hydrogen evolution pores and few surface defects.
[0093] The element distribution of the Ni-W / LDH-PMCA composite coating of Example 1 was analyzed by mapping. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the elements of the Ni-W / LDH-PMCA composite coating of Example 1 are evenly dispersed on the surface of the coating, and the electroplating effect is good.
[0094] The elemental composition and chemical state of the Ni-W / LDH-PMCA composite coating of Example 1 were observed by X-ray photoelectron spectroscopy. Figure 6 As shown. Figure 6It can be seen that the Ni-W / LDH-PMCA composite coating of Example 1 is indeed constructed from Ni-W alloy and LDH material.
[0095] The crystal structure and grain size of the coatings of Example 1 and Comparative Examples 1-2 were observed by X-ray diffractometer. The results are as follows: Figure 7 As shown. Figure 7 It can be seen that the half-peak width increases significantly after the introduction of LDH-PMCA nanosheets. According to Scherrer's formula for calculating the grain size, it can be seen that after the addition of LDH-PMCA nanosheets, the average particle size of the Ni-W / LDH-PMCA composite coating of Example 1 is reduced to the greatest extent. This is because when the nanofiller is introduced into the plating solution system, it inhibits crystal growth during the electrodeposition process and promotes the formation of more crystal nuclei, thereby reducing the grain size.
[0096] The electrochemical impedance and polarization of the coatings of Example 1 and Comparative Examples 1-2 were observed by an electrochemical workstation. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the introduction of LDH-PMCA nanosheets can greatly improve the impedance of the coating and reduce the corrosion current density, indicating that the corrosion resistance of the coating has been greatly improved. In addition, the impedance test of the coating of comparative example 3 was also carried out, and its impedance was less than 20,000 Ω·cm -2 It can only reach more than 10,000 Ω·cm -2 , while the impedance of the coating in Example 1 of the present invention can reach more than 20,000 Ω·cm -2 The corrosion resistance of the coating in Example 1 of the present invention is improved compared with the corrosion resistance of the coating in Comparative Example 3.
[0097] The coatings of Example 1 and Comparative Examples 1-2 were tested by a friction and wear tester and a microhardness tester. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the LDH-PMCA nanosheets can greatly improve the hardness and average friction coefficient of the coating, indicating that the wear resistance of the coating has been greatly improved. In addition, the coating of Comparative Example 3 was also subjected to a friction test, and its average friction coefficient was 0.391, which was higher than the average friction coefficient of 2.98 of the coating of Example 1 of the present invention. The friction performance of the coating of Example 1 of the present invention was improved by 23.79% compared with the friction performance of the coating of Comparative Example 3.
[0098] The microscopic morphology of the coatings of Example 1 and Comparative Examples 1-2 after wear was observed by SEM. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that after the introduction of LDH-PMCA nanosheets, the Ni-W / LDH-PMCA composite coating traces of Example 1 are the shallowest, and the coating surface is most completely preserved.
[0099] The three-dimensional morphology of the coatings of Example 1 and Comparative Examples 1-2 after wear was observed by a three-dimensional profile microscope. The results are as follows: Fig.11 As shown. Fig.11 It can be seen that the friction depth of the Ni-W / LDH-PMCA composite coating of Example 1 is the shallowest after the introduction of LDH-PMCA nanosheets. This is because the LDH nanosheet material itself has a self-lubricating effect, and the weaker shear should cause it to reduce friction damage through interlayer slip. During the friction process, external pressure and high temperature will cause interlayer dehydration and interlayer ion detachment in the layered material. The modified LDH nanosheet has an increase in interlayer spacing and the introduction of a larger molecular weight PMCA between the layers, resulting in a larger compression space for the material interlayer spacing. During the compression process, it will absorb part of the energy, resulting in improved wear resistance.
[0100] It should be noted that the above test examples are only partial test results of the above embodiments, and other embodiments have similar performance to that of embodiment 1, and can have better corrosion resistance, wear resistance, compactness, etc. than Ni-W coating and Ni-W / LDH composite coating. In addition, the above embodiments are only preferred embodiments of the present invention, and other embodiments of the present invention obtained by changing parameters such as agent type, dosage, temperature, time, etc. still have similar performance to the above embodiments.
[0101] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical content to make some changes or modifications to the embodiment is an equivalent embodiment of the present invention. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A Ni-W / LDH-PMCA composite coating, characterized in that: It comprises a basic coating layer and a reinforcement phase, wherein the basic coating layer is a Ni-W coating layer, and the reinforcement phase is an LDH-PMCA nanosheet.
2. The Ni-W / LDH-PMCA composite coating according to claim 1, characterized in that: In terms of weight percentage, the content of Ni is 67-72%, the content of W is 27.83-32.67%, and the content of LDH-PMCA nanosheets is 0.17-0.33%.
3. The Ni-W / LDH-PMCA composite coating according to claim 1, characterized in that: The LDH-PMCA nanosheets are obtained by the following steps: obtaining LDH nanosheets and calcining the LDH nanosheets; placing the calcined LDH nanosheets and p-methylcinnamic acid in a mixed solution of deionized water and ethanol for stirring, centrifugation and drying to obtain the LDH-PMCA nanosheets.
4. The Ni-W / LDH-PMCA composite coating according to claim 3, characterized in that: During calcination, the temperature is 450-530°C and the time is 1-3 hours; during stirring, the stirring is performed at a rotation speed of 300-500 rpm for 25-40 minutes; during centrifugation, the centrifugal speed is 7000-9000 rpm; during drying, the drying temperature is 50-70°C.
5. The Ni-W / LDH-PMCA composite coating according to claim 3, characterized in that: The mass ratio of the calcined LDH nanosheets to the p-methylcinnamic acid is 100:1.5-6; the volume ratio of the deionized water to ethanol is 1:1; and the particle size of the LDH-PMCA nanosheets is 100-200 nm.
6. A Ni-W / LDH-PMCA composite plating solution, characterized in that: The method comprises a Ni-W plating solution and LDH-PMCA nanosheets in a mass ratio of 100:0.02-0.
3.
7. The Ni-W / LDH-PMCA composite plating solution according to claim 6, characterized in that: The Ni-W plating solution is a sulfate type Ni-W plating solution or an aminosulfonate type Ni-W plating solution.
8. The Ni-W / LDH-PMCA composite plating solution according to claim 6, characterized in that: Including 10-20 g / L nickel sulfate hexahydrate, 40-55 g / L sodium tungstate dihydrate, 10-20 g / L sodium bromide or sodium fluoride, 130-160 g / L trisodium citrate dihydrate, 20-35 g / L ammonium chloride, 1-2 g / L saccharin, 0.1-0.2 g / L surfactant, and 0.2-3 g / L LDH-PMCA nanosheets; The Ni-W / LDH-PMCA composite plating solution is prepared by the following steps: Prepare a Ni-W plating solution, wherein the Ni-W plating solution includes 10-20 g / L of nickel sulfate hexahydrate, 40-55 g / L of sodium tungstate dihydrate, 10-20 g / L of sodium bromide or sodium fluoride, 130-160 g / L of trisodium citrate dihydrate, and 20-35 g / L of ammonium chloride; Weighing LDH-PMCA nanosheets at a concentration of 0.2-3 g / L, and placing them in the Ni-W plating solution, and then adding 1-2 g / L saccharin and 0.1-0.2 g / L surfactant; The Ni-W / LDH-PMCA composite plating solution was obtained by water bath ultrasonication for 15 to 20 minutes and then probe ultrasonication for 15 to 30 minutes.
9. A method for preparing a Ni-W / LDH-PMCA composite coating, characterized in that: The following steps are involved: S1: obtaining a metal substrate and pre-treating the metal substrate; S2: preparing a Ni-W / LDH-PMCA composite plating solution, and heating the Ni-W / LDH-PMCA composite plating solution to 60-80° C.; S3: placing the pretreated metal substrate into the Ni-W / LDH-PMCA composite plating solution at a temperature of 60-80° C. for electroplating to obtain the Ni-W / LDH-PMCA composite coating.
10. The method for preparing the Ni-W / LDH-PMCA composite coating according to claim 9, characterized in that: In step S3, during electroplating, the pH of the Ni-W / LDH-PMCA composite plating solution is 7-8, the stirring speed is 300-400 rpm, the temperature is 60-80°C, and the current density is 5A / dm 2 .